The Development of Problem Based Learning Method Toward Marquee Media with the Concept of HOTS - Indah Mei Diastuti; Ria Kamilah Agustina (AL-ISHLAH: Jurnal Pendidikan, 2022)
As we know that learning requires materials to support its activities. This study aims to determine the feasibility of teaching materials in the form of a book entitled Problem Based Learning (PBL) method through Marquee Media. The research method in this study is RD by Sugiono. The setting of this research was in the Hasyim Asy’ari University. The data was collected by interview and questionnaire. The data was analyzed by using expert review, limited trial, and field trial. This research resulted a textbook that not only is assessed by the expert validators but also given suggestions and input for revision improvements.